(3GdJcGed GdhXjaj ddCYeGd GdELQGFjI hGdELQGAGJ GdehGRjI (B:s (3OQGSI aj bGfhf GdeQGaYGJ GdeOfjI hGdJLGQjI (B/s - (3YeQ, fHjd ESeGYjds ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ(B, s, 2001)
(3eaghe GdJcGed GdhXjaj aj bGfhf GdeQGaYGJ,ESJNOGeGJ GdJcGed GdhXjaj aj bGfhf GdeQGaYGJ,GdCgOGa GdeQGO GdJhUd EdjgG ef GdJcGed GdhXjaj,GdfJGFL GdeJhdOI ef bjGe GdJcGed GdhXjaj GdELQGFj,OhQ GdeTQY GdELQGFj hGdbGVj hGdNUhe ERGA GdJcGed GdhXjaj,acQI GdYed GdELQGFj GdehGRj hOhQgG aj bGfhf GdeQGaYGJs
Keywords: (3bGfhf GdeQGaYGJs